Intensive Inpatient vs. Home-Based Rehabilitation After Hip Fracture in the Elderly Population - Levi, Yael; Punchik, Boris; Zikrin, Evgeniya; Shacham, David; Katz, Dori; Makulin, Evgeni; Freud, Tamar; Press, Yan (Frontiers in Medicine, 2020)
Background: As the population ages, the rate of hip fractures and the need for rehabilitation increases. Home-based rehabilitation (HBR) is an alternative to classic inpatient rehabilitation (IR), which is an expensive framework with non-negligible risks. Methods: A retrospective study of patients 65 years and above following surgery to repair a hip fracture who underwent HBR or IR between 2016 and 2019. The two rehabilitation frameworks were compared for rehabilitation outcome and factors predicting successful rehabilitation. The outcome was determined with the Montebello Rehabilitation Factor Score-Revised (MRFS-R). Results: Data were collected for 235 patients over three years. The mean age was 81.3±8.0 and 172 (73.3%) were women. Of these, 138 underwent IR and 97 HBR. The HBR group had better family support and fewer lived alone. There were also differences in the type of fracture and surgery. The medical condition of the IR group was more complex, as reflected in a higher Charlson’s comorbidity scores, higher rates for delirium and more infectious complications, a lower Norton score, lower serum hemoglobin and albumin levels, and higher serum creatinine and urea levels. It also had a more significant functional decline after surgery and required a longer rehabilitation period. However, no difference was found in the rehabilitation outcomes between the two groups (MRFS-R ≥ 50 or MRFS-R ≥ 70). The independent predictors for rehabilitation in the IR group were serum albumin level, comorbidity, and cognitive state. There were no independent predictors in the HBR group. Conclusions: In this retrospective study there was no significant difference in short-term rehabilitation outcomes between the HBR and IR groups event though the patients in the IR group were medically more complex. This result should be taken into account when planning rehabilitation services after hip fracture and tailoring rehabilitation frameworks to patients.